Hygroscopic parameters of sazan caviar as a source of lecithin and a drying object and thermodynamic analysis of the static regularities of its interaction with water - V. E. Polikarpova; I. Yu. Aleksanyan; Z. M. Arabova; A. Kh.-Kh. Nugmanov; E. Yu. Zaporozhets (Современная наука и инновации, 2023)
Increasing the efficiency of deep processing of raw materials for commercial fish farming, including caviar of freshwater fish of the carp family, which is little in demand on the Russian market. As an object of study, carp caviar was used, which is a promising source for the production of high quality natural emulsifiers, for example, lecithin. It is known that the most common method of conservation of biopolymers is the drying of raw materials. An analysis of the methods for dehydrating products like carp caviar showed that the most rational of them for this purpose is convective, with a possible combination with conductive energy supply, which predetermines the contact of the object of study with the steam-air medium and determines the expediency of determining its hygroscopic parameters for the rational organization of the drying and storage process. dried product in order to maximize the preservation of the complex of phospholipids in the product, consisting of unsaturated and saturated fatty acids, phosphoric acid, glycerol and choline, which in general is lecithin. The aim of the study was to determine the hygroscopic and thermodynamic parameters of the interaction of carp caviar with water for use in the rational implementation of the technology for its drying and obtaining lecithin from carp caviar in order to identify the conditions for maximum preservation of the necessary target component in it. Within the framework of this study, for the caviar product, its hygroscopicity, which characterizes the equilibrium moisture content of the product, was determined using the tensometric method. The obtained functional dependences of hygroscopic parameters on the influencing factors make it possible to determine the numerical values of the specific thermal energy of evaporation for their substitution into the differential heat transfer equation when modeling the drying processes of the caviar product. As a result, it can be concluded that the obtained hygroscopic and thermodynamic parameters of the caviar product can be successfully used in the rational organization and implementation of the drying technology and technique.